Answer:
A) x greater than or equal to −3
Step-by-step explanation:
We have the following inequality:
7 − 9x − (x + 12) ≤ 25
Solving the inequation, we have:
7 − 9x − x - 12 ≤ 25
-10x ≤ 30
-x ≤ 3
x≥-3
Therefore the result is option A) x greater than or equal to −3
Answer:
T
Step-by-step explanation:
Answer:
v + u
Step-by-step explanation:
Using the rule of logarithms
log x + log y ⇔ log xy
Given
ln yx, then
ln yx = ln y + ln x = v + u
Answer:
It would be -5 + -6 = 65
Step-by-step explanation:
Add it up to together by removing the -
Answer:
for the second column it is 12.5
for the third column it is 20%
for the fourth column it is 120%
for the fifth column it is 33%
for the sixth column it is 11.35
for the seventh column it is 900
for the 8th column it is 60%
for the final column it's 39
Step-by-step explanation: